Pengaruh Point Vuforia Object Scanner Terhadap Karakteristik 3D Object untuk Menampilkan Informasi Berbasis Augmented Reality - Putri Mandarani; Agung Putra Wilis; Ganda Yoga Swara (Journal of Computer System and Informatics (JoSYC), 2021)
Augmented Reality (AR) applications are one of the current mobile app trends. Its ability to display information as if to make the user merge with the information provided. The specialty of the application is in the marker. One marker that is in great demand is known as markerless, such as 3D Object Tracking. In making this 3D Object-based AR application, one must pass a stage where a real object is taken at points or known as points to be used as markers. The application used at this stage of making markers is known as the vuforia object scanner. From the experience of making AR applications, it was found conditions where markers with a large number of points were not able to display information properly, a small number of points were able to display information well and sometimes the two conditions were opposite or comparable, i.e. a lot of points makes a good marker and a few points make a bad marker. This inconsistent condition becomes a problem in this study. The test results show that the points do not affect the marker's ability to display information, but are influenced by the characteristics of the object used as the marker. Tests conducted on randomly selected objects resulted in 2 parameters to be tested in this study, namely the texture and pattern of the object. Markers with good quality to be used as markers for 3D objects are markers with a hard texture, with a detection angle of 90° and 135° and with a regular pattern